KUALITAS PELAYANAN KESEHATAN PADA KANTOR PUSKESMAS SANGKULIRANG KABUPATEN KUTAI TIMUR - Pusvasari, Rini (PREDIKSI, 2016)
In Act No. 36 of 2009 explains that health is good health, both physically, mentally, spiritually and socially to enable more people to live socially and economically productive. And also has determined that every person has the right to obtain medical care. Therefore, every element of society, both individuals, families, are entitled to services on health and responsible government launched, set up to organize and supervise the implementation of equitable and affordable health community.Â The purpose of this study was to determines the level of Health Service Quality in Health Center District Sangkulirang, Kutai Timur research approach is quantitative, the unit of analysis in this study is the individual. With descriptive quantitative method with data collection through questionnaires to patients and direct surveys to obtain data that is needed on how the quality of health services at the health center.Â Research on the health service quality in health center district Sangkulirang Kutai Timur measured using the 5 dimensions of quality public services that Tangibles, Reliability, Responsivness, Assurance and Empaty. Services carried out by the health center has been effective because it has been getting good judgment by the community based on 5 dimensions of assessment is used, it is shown with a recapitulation of the 5 dimensions of quality service has to be above 60%, this shows that the health quality service provided has been good.Â